A systematic review of the research progress of traditional Chinese medicine against pulmonary fibrosis: from a pharmacological perspective - Shanbo Qin; Peng Tan; Junjie Xie; Yongfeng Zhou; Junning Zhao (BMC, 2023)
Abstract Pulmonary fibrosis is a chronic progressive interstitial lung disease caused by a variety of etiologies. The disease can eventually lead to irreversible damage to the lung tissue structure, severely affecting respiratory function and posing a serious threat to human health. Currently, glucocorticoids and immunosuppressants are the main drugs used in the clinical treatment of pulmonary fibrosis, but their efficacy is limited and they can cause serious adverse effects. Traditional Chinese medicines have important research value and potential for clinical application in anti-pulmonary fibrosis. In recent years, more and more scientific researches have been conducted on the use of traditional Chinese medicine to improve or reduce pulmonary fibrosis, and some important breakthroughs have been made. This review paper systematically summarized the research progress of pharmacological mechanism of traditional Chinese medicines and their active compounds in improving or reducing pulmonary fibrosis. We conducted a systematic search in several main scientific databases, including PubMed, Web of Science, and Google Scholar, using keywords such as idiopathic pulmonary fibrosis, pulmonary fibrosis, interstitial pneumonia, natural products, herbal medicine, and therapeutic methods. Ultimately, 252 articles were included and systematically evaluated in this analysis. The anti-fibrotic mechanisms of these traditional Chinese medicine studies can be roughly categorized into 5 main aspects, including inhibition of epithelial-mesenchymal transition, anti-inflammatory and antioxidant effects, improvement of extracellular matrix deposition, mediation of apoptosis and autophagy, and inhibition of endoplasmic reticulum stress. The purpose of this article is to provide pharmaceutical researchers with information on the progress of scientific research on improving or reducing Pulmonary fibrosis with traditional Chinese medicine, and to provide reference for further pharmacological research.